TOOLS FOR PROMOTING LOCAL ECONOMIC DEVELOPMENT IN UKRAINE UNDER CONDITIONS OF INSTABILITY - VASYLTSIV, Taras; LEVYTSKA, Olha; KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The research emphasizes the objectively existing need, as well as the problems of ensuring local economic development in Ukraine, in particular under conditions of critically acute economic and social instability caused by a full-scale war and its consequences. The purpose of the study is to determine the scientific justification of the tools for stimulating and ensuring the local economic development of Ukraine under the instability. It is shown that in the conditions of a full-scale war, the regional socio-economic systems of Ukraine faced such challenges as large-scale external and internal migrations of the population, deepening of depopulation problems, reduction of employment and the number of jobs due to the cessation of activities or relocation of enterprises, the growth of precarization in the labor market and social and labor insecurity of vulnerable categories of the population, the development of sectoral and structural imbalances and the strengthening of personnel problems in the labor markets. Accordingly, the latest challenges have become the main causes of destabilization of the spatial development of Ukraine’s economy. The results of the analysis made it possible to identify, firstly, the significant typicality of existing problems, secondly, the significant resource limitations of local self-government bodies, thirdly, the need to involve innovative solutions, fourthly, the relevance of developing practices of intermunicipal socio-economic cooperation and integration of efforts in this way, fifthly, the need for a systemic and strategic approach, when based on visions, strategies and development programs, investment passports of territorial communities, a single coordinated regional master plan of industry specialization and development will be formed. The basic principles of two regional policy strategies in terms of stimulating local economic development are substantiated: (1) stabilization, (2) proactive. The strategic goal of each of these approaches is indicated, as well as a set of tools is defined, the implementation of which allows to activate the processes of local economic development in Ukraine under current conditions of instability.